Childhood trauma and resilience in old age: applying a context model of resilience to a sample of former indentured child laborers. (2nd June 2016) - Maercker, Andreas; Hilpert, Peter; Burri, Andrea
Abstract : Objectives: Psychological resilience has been rarely investigated in elderly populations. We applied a more comprehensive model of trauma-specific coping and resilience, which included Ungar's context model and included decentral factors of resilience (i.e., environments that provide resources to build resilience). Method: We assessed resilience in a cohort of former Swiss indentured child laborers ( N = 74; 59% males) at two time points; first at the mean age of 80 years and then again 20 months later. At each time point, the following measures of resilience were assessed: resilience indicators of life satisfaction and lack of depression. In addition, resilience predictors of trauma exposure, perceived social support, dysfunctional disclosure of traumatic experiences, social acknowledgment as a victim, and self-efficacy; and decentral resilience factors of education, income, number of children, and physical health were measured. Results: Using path-analysis, we found that life satisfaction and lack of depression were predicted by dysfunctional disclosure, social support, and self-efficacy at various significance levels. Change scores of resilience were predicted by higher trauma exposure, social acknowledgment as a victim, and an interaction between the two. The model for decentral factors also fitted, with physical health and income predicting the resilience indicators. Conclusion: Applying this comprehensive resilience model in a sample of older adults revealed meaningful findings in predicting resilience at a single time point and over time. Atypical coping strategies, such as perceived social acknowledgment as a victim and disclosure, may be particularly important for former victims who have suffered institutional abuse.